Large and Persistent Life Expectancy Disparities between India's Social Groups - Aashish Gupta; Nikkil Sudharsanan (Population and Development Review, 2022)
India is one of the most rigidly stratified societies in the world, yet little is known about life expectancy disparities in the country. We provide direct estimates of social differences in life expectancy in India using survey data spanning two decades. We show that individuals from the Scheduled Castes and Scheduled Tribes have drastically and persistently lower life expectancies than high-caste individuals (between 4.2–4.4 years for women and 6.1–7.0 years for men in 2013–2016). While Muslims had a modest life expectancy disadvantage compared to high castes in 1997–2000, this disadvantage has grown substantially over the past 20 years. Mortality disparities between marginalized and privileged social groups are present across the entire life-course and are increasingly driven by older-age mortality. Our findings reveal a pressing need for far greater attention to the health of marginalized populations in India.
Keywords: 300; caste; life expectancy; health gradients